Association of rs211037 GABRG2 gene polymorphism with susceptibility to idiopathic generalized epilepsy - Marija Milanovska; Emilija Cvetkovska; Sasho Panov (Medicinski glasnik, 2021)
Aim: This case-control study aimed to determine a possible association of single nucleotide polymorphism rs211037 of the gamma-aminobutyric acid receptor subunit gamma-2 (GABRG2) gene with the susceptibility to idiopathic generalized epilepsy (IGE) in the Macedonian population. Methods: It enrolled 96 patients with clinically verified IGE and 51 healthy individuals without personal and family history of epilepsy or other neurological disorders as controls. A determination of the GABRG2 rs211037 polymorphism was performed using the TaqMan-based genotyping assay. Results: A significant dominant association of the CC genotype (odds ratio - OR=2.100, 95% CI=1.018-4.332; p=0.043) and allelic association of C allele (OR=1.902, CI=1.040-3.477; p=0.035) with susceptibility to IGE was found. Carriers of CC genotype had approximately a 2-fold higher probability of developing IGE than the carriers of CT and TT genotypes. Carriers of the C allele had a 1.9-folds higher probability for IGE than the carriers of the T allele. Conclusion: The polymorphism rs211037 of the GABRG2 gene increases the risk of the development of idiopathic generalized epilepsy in the Macedonian population.
Keywords: case control studies; epilepsy; GABA receptors; single nucleotide polymorphism